Association Between Breast Cancer Disease Progression and Workplace Productivity in the United States. Issue 2 (February 2017) - Yin, Wesley; Horblyuk, Ruslan; Perkins, Julia Jane; Sison, Steve; Smith, Greg; Snider, Julia Thornton; Wu, Yanyu; Philipson, Tomas J.
Abstract : Objective: Determine workplace productivity losses attributable to breast cancer progression. Methods: Longitudinal analysis linking 2005 to 2012 medical and pharmacy claims and workplace absence data in the US patients were commercially insured women aged 18 to 64 diagnosed with breast cancer. Productivity was measured as employment status and total quarterly workplace hours missed, and valued using average US wages. Results: Six thousand four hundred and nine women were included. Breast cancer progression was associated with a lower probability of employment (hazard ratio [HR] = 0.65, P < 0.01) and increased workplace hours missed. The annual value of missed work was 24, 166 for non-metastatic and 30, 666 for metastatic patients. Thus, progression to metastatic disease is associated with an additional 6500 in lost work time ( P < 0.05), or 14% of average US wages. Conclusions: Breast cancer progression leads to diminished likelihood of employment, increased workplace hours missed, and increased cost burden. Abstract : Supplemental Digital Content is available in the text